REVISITING REALISTIC JOB PREVIEW FOR RECRUITMENT: A THEORETICAL PERSPECTIVE - Putu Chris Susanto; Listiyani Dewi Hartika (Faculty of Economics and Business Udayana University, 2016)
This paper aims to revisit the theoretical concepts of Realistic Job Preview (RJP), as a human resource management approach to provide job candidates with information to better match the candidates’ expectations with therealities regarding the job. Further, the paper attempts to present several considerations and strategies in implementing RJP in the socialization, selection, and retention processes of recruitment. The theoretical reviewpresented shows that, when given properly and at the correct timing, RJP could increase job satisfaction, commitment, and performance while reducing turnover. This implies that the information shared through RJP could create a more realistic, deflated expectation about the job and the organization when presented using multiple formats